Identification of apple diseases in digital images by using the Gaining-sharing knowledge-based algorithm for multilevel thresholding - Noe O.-S. Ortega-Sanchez; Rodriguez-Esparza E. Erick; Oliva Navarro D. A. Diego Alberto; Marco P.-C. Perez-Cisneros; Wagdy M. A. Mohamed Ali; Gaurav Dh. Dhima; Hernandez-Montelongo R. Rosaura (2022, 2022)
Title screen